Age: A Moderating Effect on Cerebrospinal Fluid Fibroblast Growth Factor 21 and Cognitive Function - Ligang Shan; Ying Tao; Jiubo Fan; Yuyu Zhou; Danyang Zhao; Yanlong Liu; Xiaoli Han; Suriyakala Perumal Chandran; Fan Wang (Brain and Behavior)
ABSTRACT Background Fibroblast growth factors(FGF)19 subclass related to endocrine metabolism, including FGF19, FGF21, and FGF23, which is associated with cognition. Age can affect its secretion and has been identified as a significant risk factor for cognitive decline. Consequently, age may moderate the impact of the FGF19 subclass on cognitive function. This study aimed to investigate the association among the FGF19 subclass in cerebrospinal fluid (CSF), cognition, and age and further explore the moderating effects of age on cognitive changes related to the FGF19 subclass. Methods In this cross‐sectional study, participants were stratified into two groups based on age, namely the ≤34 year old (n = 128) and >34 year old (n = 63) groups, and CSF FGF19 subclass levels were measured. Cognition was assessed using the Montreal Cognitive Assessment Scores. Results Age may play a moderating effect in the relationship between CSF FGF21 and cognition (R2 = 0.12, β = ‐0.32, p  = 0.003). In individuals aged >34 years old, a negative correlation was observed between serum TG levels and MoCA scores (r = ‐0.31, p = .041). Contrastingly, no correlation was noted between CSF FGF19 and CSF FGF23 levels with MoCA scores in both groups, respectively (all p > 0.05). Conclusions This is the first study to report that age plays a moderating effect in the relationship between CSF FGF21 and cognition. Moreover, higher CSF FGF21 levels have a protective effect on cognition in individuals aged ≤34 years old. However, individuals aged>34 years old can improve cognition via alternative strategies.